PENGARUH NEUROMUSCULAR TAPING PADA CORE STABILITY EXERCISE TERHADAP SENSASI NYERI KASUS MYOGENIC LOW BACK PAIN - Achmad Banu Mustofa; Heri Priatna; Abdurrasyid Abdurrasyid; Jerry Maratis (LPPM Universitas Abdurrab, 2024)
ABSTRACT Objective: To investigate the disparity in the impact of neuromuscular taping versus core stability exercise on pain perception in individuals with myogenic low back pain. Method: This study employed a quantitative technique utilising a quasi-experimental pretest-posttest control group design. The Visual Analogue Scale (VAS) was utilised to quantify pain. 22 samples were chosen using purposive sampling based on preset criteria. Results: of the hypothesis I and II testing, conducted using the related t-test, yielded a P-value of 0.000. Additionally, the hypothesis III testing, performed using the independent t-test, resulted in a P-value of 0.001. The average decrease in pain perception in group I was 35.09, while in group II it was 42.27. Conclusion: Utilising neuromuscular tapping in core stability exercise yields superior results in reducing pain sensation in individuals with myogenic low back pain compared to core stability exercise alone. Keywords: Neuromuscular Taping, Core Stability Exercise, Visual Analogue Scale (VAS), Myogenic Low Back Pain.